2012
DOI: 10.33762/bvetr.2012.54769
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Kerato-Counjunctivitis in Local Buffaloes Breeds in Mosul, Mosul- Iraq

Abstract: ABSTRUCTThe objective of this study was to investigate infectious keratoconjunctivitis in local buffaloes breed in Mosul (Mosul-Iraq). The study was conducted on (360) local buffaloes breed of different ages and both sexes. Animals were belong to different privet farms in Mosul area, and reared indoor or grazed during the day light. Result revealed that out of (360) animals, (80) animals have been exhibited the clinical sings of keratoconjusnctivitis, with a prevalence rate of (22.2%). Diseased animals show si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…was diagnosed in blood smears from cattle only. In Mosul, however, Anaplasma marginale has been identified in buffalo [ 26 ], camel [ 27 ], while Anaplasma ovis was detected in goats [ 5 , 14 ], in addition to that reported in cattle [ 3 , 28 ]. Nevertheless, no previous study has reported the percentage of infection among other blood parasites except that for Al-Abadi and Al-Badrani [ 2 ] in cattle at 4.4%, which is lower than that reported in the study conducted here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…was diagnosed in blood smears from cattle only. In Mosul, however, Anaplasma marginale has been identified in buffalo [ 26 ], camel [ 27 ], while Anaplasma ovis was detected in goats [ 5 , 14 ], in addition to that reported in cattle [ 3 , 28 ]. Nevertheless, no previous study has reported the percentage of infection among other blood parasites except that for Al-Abadi and Al-Badrani [ 2 ] in cattle at 4.4%, which is lower than that reported in the study conducted here.…”
Section: Discussionmentioning
confidence: 99%
“…were identified in blood smears [ 2 ]. Previous studies diagnosed Anaplasma marginale in cows [ 3 ], Theileria hirci in local sheep [ 4 ], Theileria hirci and Anaplasma ovis in local goats [ 5 ], Babesia equi and Babesia caballi in horses [ 6 ], and Babesia caballi in camels [ 7 ].…”
Section: Introductionmentioning
confidence: 99%